2019
DOI: 10.1002/ece3.5085
|View full text |Cite
|
Sign up to set email alerts
|

Habitat usage of Daubenton's bat (Myotis daubentonii), common pipistrelle (Pipistrellus pipistrellus), and soprano pipistrelle (Pipistrellus pygmaeus) in a North Wales upland river catchment

Abstract: Distributions of Daubenton's bat ( Myotis daubentonii ), common pipistrelle, ( Pipistrellus pipistrellus ), and soprano pipistrelle ( Pipistrellus pygmaeus ) were investigated along and altitudinal gradient of the Lledr River, Conwy, North Wales, and presence assessed in relation to the water surface condition, presence/absence of bank‐side trees, and elevation. Ultrasound recordings of bats made on timed transects in summer 1999 were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Their riparian vegetation and water surface are important foraging areas for many bat species and are recognized as determinants to explain bat abundance across the landscape (Grindal et al, 1999;Downs & Racey, 2006;Lloyd et al, 2006;Lookingbill et al, 2010;Sirami et al, 2013;Carrasco-Rueda & Loiselle, 2019). In highly urbanized areas rivers or waterways and their associated riparian vegetation are often the only corridors still relatively dark, and are thus of high importance for bat moving through such illuminated landscapes (Lintott et al, 2015;Laforge et al, 2019;Todd & Williamson, 2019). However, ecological consequences of the illumination of rivers remain largely understudied (Jechow & Hölker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their riparian vegetation and water surface are important foraging areas for many bat species and are recognized as determinants to explain bat abundance across the landscape (Grindal et al, 1999;Downs & Racey, 2006;Lloyd et al, 2006;Lookingbill et al, 2010;Sirami et al, 2013;Carrasco-Rueda & Loiselle, 2019). In highly urbanized areas rivers or waterways and their associated riparian vegetation are often the only corridors still relatively dark, and are thus of high importance for bat moving through such illuminated landscapes (Lintott et al, 2015;Laforge et al, 2019;Todd & Williamson, 2019). However, ecological consequences of the illumination of rivers remain largely understudied (Jechow & Hölker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This challenge was also supported by the acoustics model that included the total QBR score as an explanatory variable, in which the geomorphological type of the river bank seemed to affect the resulting bat activity (Table S3). Surprisingly, none of our final models included river width nor water speed, while other studies have shown that both variables are extremely important in selecting the most appropriate hunting grounds (Almenar et al, 2009;L opez-Baucells et al, 2017;Todd & Williamson, 2019).…”
Section: Acoustic Versus Visual Counts Sampling Protocolsmentioning
confidence: 84%
“…Similarly, while visual counts can certainly be assigned to trawling bats, our study area presented two different trawling bat species, Myotis daubentonii and Myotis capaccinii, (as seen in Blanch et al, 2023), that cannot be distinguished through visual detections. While these two species differ in roost selection, studies on foraging habitat use have previously found that both species usually select forested riparian habitats (Almenar et al, 2006;de Conno et al, 2018;Todd & Williamson, 2019;Warren et al, 2000), rather than non-vegetated river transects, so their potential as riverine forest bioindicator could be similar. However, more thorough research would still be needed to discern specific differences between them.…”
Section: Acoustic Versus Visual Counts Sampling Protocolsmentioning
confidence: 99%
“…5D). Subsequently, with increased clutter on these water surfaces, bats were prevented from accessing them and would have to seek water from alternative sources to persist in the area [21]. As proposed in the study by Nystrom and Bennett [14], when temperatures exceeded a certain threshold bats would utilize residential swimming pools as an alternative resource.…”
Section: Discussionmentioning
confidence: 99%